2017
DOI: 10.3389/fpsyt.2017.00134
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits Related to Binge Drinking: A Systematic Review

Abstract: The pattern of alcohol consumption in the form of binge drinking (BD) or heavy episodic drinking has increased notably worldwide in recent years, especially among adolescent and young people, being currently recognized as a global health problem. Although only a minority of binge drinkers will develop a substance use disorder, BD may have negative personal and social consequences in the short and medium term. The objective of this article is to review the findings on personality traits related to binge drinker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
113
3
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 53 publications
6
113
3
10
Order By: Relevance
“…Another potential shared risk factor, noted by the authors, is personality. This aligns with extensive research showing that personality is associated strongly with smoking and alcohol use , as well as caffeine intake . Most notable are the personality traits impulsiveness, sensation‐seeking and extraversion.…”
supporting
confidence: 86%
“…Another potential shared risk factor, noted by the authors, is personality. This aligns with extensive research showing that personality is associated strongly with smoking and alcohol use , as well as caffeine intake . Most notable are the personality traits impulsiveness, sensation‐seeking and extraversion.…”
supporting
confidence: 86%
“…Evidence for the utility of impulsivity‐specific (eg, BIS‐11) versus broad trait personality measures (eg, NEO‐FFI) for statistical prediction of alcohol is mixed. Adan and colleagues reviewed personality correlates of binge drinking across studies and found that high impulsivity, as well as anxiety sensitivity, neuroticism, extraversion, and low conscientiousness across studies, were most strongly related to binge drinking. We examined this in model 2 (all non‐ERP variables) and found that high anxiety symptoms, followed by high impulsivity (Stroop interference effect; BIS‐11 Nonplanning and Motor subscales; IRV), high Agreeableness and lower Neuroticism and Conscientiousness were linked to greater alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…These include increased symptoms of depression, anxiety, and stress among university students, with increasing evidence suggesting that impulsive behaviors are affected by affective states . Furthermore, personality traits are important factors in determining alcohol‐related trajectories yet are rarely examined in conjunction with more specific impulsive traits . Self‐reported–trait impulsivity, as measured by the Barratt Impulsiveness Scale 11th version (BIS‐11), is strongly linked to alcohol use, alcohol‐related problems, and early‐onset disordered use .…”
Section: Introductionmentioning
confidence: 99%
“…Around 5.9-7.1% of children and adolescents and 5.0% of adults are thought to meet the diagnostic criteria for ADHD 2 , and genetic studies support the notion that a clinical diagnosis represents the extreme end of a continuum of impulsivity and/or attention problems in the general population 3,4 . Both ADHD diagnosis and higher levels of impulsivity and attention problems are associated with higher levels of cigarette smoking 5,6 , cannabis use 7,8 , alcohol use 7,9 and caffeine consumption 10,11 . The exact nature of these associations is not fully understood, which hampers the development of evidence-based interventions and public health messages.…”
Section: Introductionmentioning
confidence: 99%